Komposisi Kandungan Asam Amino Pada Teripang Emas (Stichoupus horens) di Perairan Pulau Bintan, Kepulauan Riau - Gianto Gianto; Made Suhandana; R. Marwita Sari Putri (Universitas Sriwijaya, 2017)
This study aims to analyze the amino acid component contained in the golden sea cucumber so that it can be used as a basis for consideration, management, especially the development of sea cucumbers. Protein in sea cucumbers have complete amino acids, both essential amino acids and non-essential amino acids. The result of the proximate test of golden sea cucumber has high protein content which is 95,14% and fat 0,20% compared to other sea cucumber type while the protein of sea cucumber is very low that is 1.78% and 1.54% ash. The highest content of dried sea cucumber amino acids in golden sea cucumber meat seen in glutamic acid of 6.6049%, 7.1769% glycine, aspartic acid 3.9227% and proline of 3.4189% while the results of wet sea cucumber amino acids have a low amino acid value with glutamic acid 0.2281%, Glycine 0.2308% and Alanin 0.2169%.